Evaluation of design criteria for inflow and infiltratration of medium scale sewerage catchment system - 213502 Dayalan Rainoo Raj; Norhan Abd. Rahman, supervisor; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Hidraul dan Hidrologi)) - Universiti Teknologi Malaysia, 2007